(untitled) (Journal for Studies in Humanities and Social Sciences, 2016)
There is widespread concern about the outcomes of science education in Namibian schools. The representatives of industries say that they need high-grade scientists, technicians and engineers if Namibia is to successfully compete in technology-intensive global markets by 2030. Ethno-science is a specialisation of indigenous knowledge (IK). It focuses on a scientific perspective of culture. The re-search that resulted in this article critically analysed the relevance of integrating ethno-science (IK) into the Upper Primary School curriculum in Namibia. The research further looked at how the people in the Zambezi region have developed a working terminology that produces taxonomies related to ethno-science. Research has shown that most anthropologists have carried out studies in ethno-science based on native perceptions. This research relies on a quantitative research approach in order to gather data from a population on the general understanding of ethno-science. It can also reveal that 10 parents were involved in the research. This research is of the utmost importance to the different sectors of the industry, teachers, learners, the National Institute For Educational Development (NIED), parents and institutions of higher learning as well as for the nation that needs to produce more science specialists at all level; a society that needs technicians as well as world-class researchers in order to increase the public’s ability to engage with scientific knowledge and choices.